Family Ownership, Institutional Ownership, and Internationalization of SMEs1. (19th August 2013) - Chen, Hsiang‐Lan; Hsu, Wen‐Tsung; Chang, Chiao‐Yi; Karatas‐Ozkan, Mine; Anderson, Alistair R.; Fayolle, Alain; Howells, Jeremy; Condor, Roland
<x xml:space="preserve">Abstract</x> Family ownership has been recognized as an important determinant of corporate strategic choices; however, little research investigates the effects of family ownership and corporate governance on internationalization in small and medium‐sized enterprises (SMEs). This paper utilizes agency theory and the resource‐based view to analyze the relationships between family ownership, institutional ownership, and internationalization. Using a sample of Taiwanese SMEs, the finding of a positive family ownership–internationalization relationship suggests that family ownership may encourage internationalization. The interaction of family ownership and institutional ownership is positively related to internationalization, suggesting that SMEs with high family ownership are more likely to internationalize as institutional ownership increases.